Giải các pt sau:
a) \(\sqrt{x+8}+\frac{9x}{\sqrt{x+8}}-6\sqrt{x}=0\)
b) \(x^4-2x^3+\sqrt{2x^3+x^2+2}-2=0\)
c) \(3x\sqrt[3]{x+7}\left(x+\sqrt[3]{x+7}\right)=7x^3+12x^2+5x-6\)
d) \(4x^2+\left(8x-4\right)\sqrt{x}-1=3x+2\sqrt{2x^2+5x-3}\)
e) \(16x^2+19x+7+4\sqrt{-3x^2+5x+2}=\left(8x+2\right)\left(\sqrt{2-x}+2\sqrt{3x+1}\right)\)
f) \(\left(5x+8\right)\sqrt{2x-1}+7x\sqrt{x+3}=9x+8-\left(x+26\right)\sqrt{x-1}\)
g) \(\sqrt[3]{3x+1}+\sqrt[3]{5-x}+\sqrt[3]{2x-9}-\sqrt[3]{4x-3}=0\)
Giải PT: \(\sqrt{x^2+2x}+\sqrt{9x-3}=\sqrt{4x^2+13x+3}\)
Giải PT: \(\sqrt{2x^2-9x+4}+3\sqrt{2x-1}=\sqrt{2x^2+21x-11}\)
Giải PT: \(\sqrt{2x^2-9x+4}+3\sqrt{2x-1}=\sqrt{2x^2+21x-11}\)
Giải PT a, \(5\sqrt{2x^2+3x+9}=2x^2+3x+3\)
b. \(9-\sqrt{81-7x^3}=\frac{x^3}{2}\)
c. \(x^2+3-\sqrt{2x^2-3x+2}=\frac{3}{2}\left(x+1\right)\)
d. \(\sqrt{9x-2x^2}-9x+2x^2+6=0\)
e. \(\sqrt{x^2+x-1}+\sqrt{x-x^2+1}=x^2-x+2\)
f. \(\sqrt{x^2+x-5}+\sqrt{x-x^2+3}=x^2-3x+4\)
Tìm x :
h/ \(\sqrt{x+5}-10=-4\)
i/ \(\sqrt{x-5}+2\sqrt{4x-20}-\frac{1}{3}\sqrt{9x-45}=12\)
j/ \(3\sqrt{2x}+\frac{1}{7}\sqrt{98x}-\sqrt{72x}+4=0\)
k/ \(\sqrt{4x^2-20}-\frac{1}{3}\sqrt{x^2-5}+\sqrt{\frac{9x^2-45}{16}}-\frac{1}{2}\sqrt{\frac{25x^2-125}{36}}=4\)
l/ \(\sqrt{4x+4}+\sqrt{9x+9}-\sqrt{x+1}=4\)
m/ \(\sqrt{16\left(x+1\right)}+\sqrt{4x+4}=16-\sqrt{x+1}+\sqrt{9x+9}\)
Giúp mk với nhé mn
Giải pt \(x^3+12x+7\sqrt{x+2}+7\sqrt{8-x}=6x^2+9\)
Giải pt:
\(x^2-4x+6=\sqrt{2x^2-5x+3}+\sqrt{-3x^2+9x-5}\)
Giải PT:
a) x2+y2+\(\frac{1}{x^2}\)+\(\frac{1}{y^2}\)=4
b) \(\sqrt{3x^2+12x+13}+\sqrt{2x^2+8x+17}=4\)